Traders' Perceptions of Market Facilities and Infrastructure Policies in Lubuk Buaya - Padang City - Elfandra Fan Fadhli Rabbi; Aldri Frinaldi; Rembrandt Rembrandt (Science and Environmental Journal for Postgraduate, 2024)
This study focuses on traders' perceptions of the facility and infrastructure policy in the Lubuk Buaya traditional market. Based on the research questions, this type of research is qualitative descriptive research. The research informants were traders with the Snowball Sampling sampling technique and data were collected through observation and interviews. The results of the study showed that most traders did not know about Padang Mayor Regulation No. 7/2022. However, the use of facilities and infrastructure is up to government expectations even though there are some shortcomings. The effectiveness of the policy can be seen from the optimal utilization of facilities, but efficiency still needs to be improved, especially in terms of security and collection of levies. The adequacy of facilities is also adequate even though there are obstacles to trash bins. This policy is successful in terms of equality and government response to traders' needs. The accuracy of the policy can be seen from the positive impact of the maximum use of facilities.